2021
DOI: 10.2147/jbm.s291394
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sickle Cell Disease Complications Beyond Acute Chest Syndrome

Abstract: Sickle cell disease results in numerous complications that can lead to significant morbidity and mortality. Amongst them, acute chest syndrome is the leading cause of mortality. As a result, most providers are in tune with this complication and well versed with management. As sickle cell patients now live longer, they face a multitude of other complications that if left unattended, can lead to significant morbidity and mortality as well. It is critical to look beyond acute chest syndrome and adopt a more compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…In settings where drug abuse co-exists with structural racism and poverty, the need for opioids to manage pain is often met with resistance. 36 On the other hand, opioid related disorders have been described to be higher among SCD pregnant woman than in those without SCD and significantly impact maternal sepsis and other pregnancy outcomes. 37 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In settings where drug abuse co-exists with structural racism and poverty, the need for opioids to manage pain is often met with resistance. 36 On the other hand, opioid related disorders have been described to be higher among SCD pregnant woman than in those without SCD and significantly impact maternal sepsis and other pregnancy outcomes. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Given the systematic inequity endured by the affected population, many of these novel strategies will be beyond their reach, especially in developing countries. 36 A systematic review by Sins et al. of controlled clinical trials of pharmaco-therapeutical interventions to reduce VOCs in SCD patients found that the most promising interventions to reduce VOC frequency or hospitalizations were the oral antioxidants L-glutamine and ω−3 fatty acids, and the intravenous antiadhesive agent, crizanlizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious complications include the onset of acute chest syndrome (ACS), avascular necrosis, hemolytic anemia, silent cerebral infarction, inflammation, priapism, and stroke. Moreover, serious complications often revolve around organ damage, eventually resulting in organ failure, including renal failure [ 2 , 3 ]. Apart from the disease complications, treatment-related adverse effects also occur, especially in those who require frequent blood transfusions, most commonly presenting as TRALI [ 5 ].…”
Section: Reviewmentioning
confidence: 99%
“…Due to their deformed shape, sickle cells tend to become trapped within small vessels and deprive the tissues of blood that is rich in oxygen [ 2 ]. The onset of SCD is often accompanied by various complications, including hemolytic anemia, reduced immunity, inflammation, acute/chronic organ damage, and stroke, among others [ 3 ]. Therefore, providing effective treatment to patients impacted by SCD is critical.…”
Section: Introductionmentioning
confidence: 99%